(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2025)
About twenty years ago, a number of researchers proposed interpreting certain works and artists in relation to a category apparently distant from the concept of waste or reject: the sublime. What I attempt to do in this paper is to investigate: a) how a link can be established between the sublime and contemporary art; b) how contemporary art can express the sublime through the use of materials and sounds that are considered ‘waste’; c) to what extent this use can take on a critical-political significance.